Determinants of Motorized Two-Wheeler Crash Injuries in Lahore, Pakistan: A Hospital-Based Study - Amjad Iqbal Burq, Muhammad Saleem Rana, Ejaz Ahmed Qureshi (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Road traffic accidents (RTAs) are a leading cause of morbidity and mortality worldwide, with motorcycle riders being among the most vulnerable road users. In Pakistan, motorcycles are the most common mode of transport, but high crash rates impose a substantial burden on the healthcare system. Despite this, limited research has explored the combined role of demographic, behavioral, vehicular, and environmental determinants of motorcycle crash outcomes. Objective: To identify the demographic, behavioral, vehicular, and environmental determinants of motorized two-wheeler crash injuries in Lahore, Pakistan. Methods: A cross-sectional descriptive study was conducted at the trauma centers of Mayo Hospital, Jinnah Hospital, and Lahore General Hospital between April and June 2022. Using non-probability convenience sampling, 295 injured or deceased motorcycle riders were enrolled. Eligible participants included riders of any age or gender involved in road traffic crashes, while individuals with non-road trauma such as falls or assaults were excluded. Data were collected through a structured proforma and analyzed descriptively. Results: Most victims were working-age riders (17–60 years), highlighting occupational and commuting exposure. Adolescents (<17 years) exhibited high-risk behaviors, particularly stunt riding. Evening commuting hours accounted for the majority of crashes. Helmet non-use, frequently linked to thermal discomfort, significantly increased injury severity. The majority of motorcycles were in serviceable condition, suggesting behavioral rather than mechanical causes. Human error, including over-speeding and traffic violations, emerged as the most significant determinant of crashes. Conclusion: Motorcycle crash outcomes in Lahore are shaped primarily by demographic and behavioral factors, compounded by environmental risks. Targeted interventions including adolescent-focused safety programs, climate-appropriate helmets, and stricter enforcement of traffic laws are urgently needed. Keywords: Motorized two-wheeler, crash injuries, helmet use, behavioral risk factors, road safety.